PEMBERDAYAAN MAHASISWA MELALUI ENTREPRENEURSHIP SKILLS - Novius, Andri; Syafei, Jasmina; Lusiawati, Lusiawati; Elisanovi, Elisanovi (Fokus ABDIMAS, 2023)
This community service activity aims to empower college students through the development of entrepreneurship skills. In the era of globalization and intense job competition, empowering students is an important key to facing economic challenges and creating jobs.The method used in this activity includes the identification and selection of college students based on their interests and motivation towards entrepreneurship. Selected students will take part in a series of training covering the basics of entrepreneurship, business planning, financial management, marketing, innovation, and communication skills. In addition, students will also receive guidance and assistance from experienced lecturers or business practitioners. They will be guided in developing business ideas and developing business plans.Assistance is also provided in business development, including the process of establishing a business, operational management, and developing networks with local communities and other related parties. Evaluation and monitoring are regularly carried out to measure the progress of students and monitor the development of businesses founded by them.The results of this activity will be disseminated through publications, counseling, seminars, and collaboration with related parties. It is hoped that student empowerment through entrepreneurship will provide benefits in the form of increased job opportunities for students, contribution to the local economy, and development of student capacity in facing the world of work. This activity is also a strategic step in improving the quality of higher education and creating an ecosystem that is conducive to entrepreneurship. By involving students in this empowerment activity, it is hoped that a young generation will be created who are creative, innovative, and ready to face future challenges.Keywords: entrepreneurship skills, empowering college students.